Debridement, antibiotics and implant retention (DAIR): An effective treatment option for early prosthetic joint infections. Issue 8 (August 2021) - Tatarelli, P.; Romani, T.; Santoro, V.; Spezia, M.; Gallo, A.; Ripamonti, G.; Carducci, M.; Trotti, C.; Parisini, A.; Nicolini, L.A.; Mikulska, M.; Borrè, S.; et al.
Abstract: Introduction: Debridement, antibiotics and implant retention (DAIR) is an attractive treatment option for prosthetic joint infections (PJIs). However, reported success rates and predictors of DAIR failure vary widely. The primary aim of this study is to report the outcome of DAIR in patients with hip and knee PJIs receiving short course of antibiotic therapy. The secondary aim is to identify risk factors for DAIR failure. Methods: We performed a retrospective analysis of prospectively collected data of all hip and knee PJIs consecutively diagnosed at Quadrante Orthopedic Center, an Italian orthopedic hospital highly specialized in prosthetic surgery, from January 1, 2013 to January 1, 2019, and we analyzed those treated with DAIR. Results: Forty-seven PJIs occurred after 5102 arthroplasty procedures. Twenty-one patients (45%) aged 71 years were treated with DAIR for hip (62%) and knee (38%) PJIs. These were classified as early PJIs in 76% cases, delayed in 19% and late in 5%. Median time from PJI-related symptoms onset to implant revision surgery was 12 days (IQR, 7–20 days). The median duration of antibiotic treatment after surgery was 63 days (IQR, 53–84 days). Sixteen (76%) patients were cured after a median follow-up of 2197 days (IQR, 815–2342 days), while 5 (24%) experienced failure. At multivariate analysis, delayed/late PJIs were significantly associated with failure (OR = 12.51; 95% CI 1.21–129.63, p = 0.03). Conclusions: DAIR represents an effective strategy for the treatment of early PJIs in spite of short course of antibiotic therapy.